Constructing and Standardizing A Test For Measuring Legs’ Vertical Strength Defined by Speed in Youth Basketball - Sami Yousif , Faris; Jabbar , Abdaljaleel; Ahmed , Elaf (Journal of Physical Education, 2012)
The tests that measure special strength defined by speed contributes a great deal in evaluating the players’ weaknesses and strengths so as to aid coaches judge their players according to scientific and objective measurements. The problem of the study lies in answering the following question : is there a test that measures legs’ vertical strength defined by speed especially for youth basketball players? The aim of the research was to construct and standardize a test for measuring legs’ vertical strength defined by speed in youth basketball. The subjects of the study were 74 youth basketball players from Baghdad. The researchers concluded that the test measures leg’s vertical strength defined by speed for youth basketball players as well as it sets the criteria for these tests. Finally the researchers recommended using this test for measuring leg’s vertical strength defined by speed in the evaluation process in addition to the criteria of this research as a reference for selecting youth basketball players. Finally the researchers recommended making similar researches using other physical variables not studied in this research.